Coffee drink consumption pattern and its contribution of calcium and caffeine intake related to bone status in college students in Korea - Choi, In-Young; Kim, Mi-Hyun (Progress in Nutrition, 2023)
Background and aim: Coffee consumption is steadily increasing especially among young adults in Korea. This study aimed to investigate the coffee drink consumption and its association with calcium and caffeine intake related to bone in young adults.Methods: A total of 145 male and 156 female college students aged 19–29 years participated in the study. Anthropometric measurements and a questionnaire survey were conducted. Bone mineral density (BMD) of the calcaneus was measured using quantitative ultrasound. The study participants were divided into three groups according to their coffee consumption status: high–coffee group (HC≥median of daily intake), low coffee group (LC